Fixed-order decentralized/distributed control of islanded inverter-interfaced microgrids. (December 2015) - Sadabadi, Mahdieh S.; Karimi, Alireza; Karimi, Houshang
Abstract: This paper focuses on the problem of voltage control of islanded inverter-interfaced microgrids consisting of several distributed generation (DG) units with radial structure. The main objectives are to (i) design a decentralized/distributed voltage controller with minimum information exchange between DG units and their local controllers (ii) design a fixed-/low-order dynamic output feedback controller which ensures stability as well as desired performance of the microgrid system in spite of load parameter uncertainties. To this end, the problem is formulated as an optimization problem which is the minimization of the cardinality of a pattern matrix subject to an H ∞ performance constraint. Since the problem is intrinsically non-convex, a convex optimization-based design procedure for the controller synthesis is proposed in this paper. The effectiveness of the proposed controller is evaluated through simulation studies and Hardware-In-the-Loop (HIL) verifications. The simulation and experimental results demonstrate the effectiveness of the proposed control strategy. Abstract : Highlights: Voltage control of islanded inverter-interfaced microgrids with radial structure. Trade-off between control performance and DG communications. Fixed-structure voltage control of microgrids with load parameter uncertainties.